IP MULTICAST APPLICATIONS BETWEEN SERVERS AND CLIENTS - Dwiyanti Woro Astuti; Ir. Rafael A. Gafar, MM (Jurnal Sistem Informasi, 1998)
IP multicast is used to classify the information needs of different clients as well to avoid any intruders and attacks using IP addresses in a group or groups that can improve network security. Based multicast the TCP / IP more widely used than other types of network architecture for faster observations, TCP / IP protocol that is routable (can be in-routing) and reliable in terms of network resources can reduce the load and overload will not occur when the server receives data requests from the client because it has error correction control.